Effectiveness of information and communication technology-based integrated care for older adults: a systematic review and meta-analysis - Tian, Yutong; Wang, Shanshan; Zhang, Yan; Meng, Lixue; Li, Xiaohua (Frontiers in Public Health, 2024)
Background Information and communication technology (ICT) is a key factor in advancing the implementation of integrated care for older adults in the context of an aging society and the normalization of epidemics. This systematic review aims to comprehensively evaluate the effectiveness of ICT-based integrated care for older adults to provide input for the construction of intelligent integrated care models suitable for the context of an aging population in China. Methods A systematic review and meta-analysis were conducted using PubMed, Web of Science Core Collection, Scopus, MEDLINE, EBSCO, EMBASE, CINAHL with full text, ProQuest, and Cochrane Library databases, along with the Google Scholar search engine, for papers published between January 1, 2000, and July 25, 2022, to include randomized controlled trials and quasi-experimental studies of ICT-based integrated care for older adults. Two reviewers independently performed literature screening, quality assessment (JBI standardized critical appraisal tool), and data extraction. The results were pooled using a random effects model, and narrative synthesis was used for studies with insufficient outcome data. Results We included 32 studies (21 interventions) with a total of 30,200 participants (14,289 in the control group and 15,911 in the intervention group). However, the quality of the literature could be improved. The meta-analysis results showed that ICT-based integrated care significantly improved the overall perceived health status of older adults (n=3 studies, MD 1.29 (CI 0.11 to 2.46), no heterogeneity) and reduced the number of emergency department visits (n=11 studies, OR 0.46 (CI 0.25 to 0.86), high heterogeneity) but had no significant effect on improving quality of life, mobility, depression, hospital admissions and readmissions, or mortality in older adults, with a high degree of study heterogeneity. Narrative analysis showed that the overall quality of care, primary care service use, and functional status of older adults in the intervention group improved, but the cost-effectiveness was unclear. Conclusions ICT-based integrated care is effective in improving health outcomes for older adults, but the quality and homogeneity of the evidence base need to be improved. Researchers should develop intelligent integrated care programs in the context of local health and care welfare provision systems for older adults, along with the preferences and priorities of the older adults.